Women’s Practical Roles in the Historical Context of Islamic Society - Sami Ur Rehman; Talal Nawaz Janjua (Journal of Religion and Society, 2025)
Women are the pillars of the society. Empowering woman by education, equal opportunities and legal protection benefits the whole nation. The future lies in providing opportunities to woman to build a just and progressive society. However, these must be in line with the boundaries set by Islam. The research is basically a collection of data from primarily sources. It depicts the position of woman in and after the time of Prophet (Peace Be Upon Him) life, in social, economic, educational, administrative domains. Quantitative methodology has been used. It is clearly visible that Islam has given conditional permission to women to participate in various practical activities of life. Muslim woman have played a major role in spreading the religion. It is permissible for females to participate actively in various charitable activities while running her household chores as well. Voice of logic has been always accepted even if it comes from female side. The Islamic history highlights incidents where woman have participated in war for the exaltation of Islam. Keywords: Woman, Role of Woman in Islam, Social, Economic, Educational, Administrative